Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1093/pm/pnv020
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Double-Dummy Study to Evaluate the Intranasal Human Abuse Potential and Pharmacokinetics of a Novel Extended-Release Abuse-Deterrent Formulation of Oxycodone

Abstract: Objective. Evaluate the human abuse potential (HAP) of an experimental, microsphere-in-capsule formulation of extended-release oxycodone (oxycodone DETERx®) (herein “DETERx”).Design. Randomized, double-blind, double-dummy, positive- and placebo-controlled, single-dose, four-phase, four-treatment, crossover study.Setting. Clinical research site.Subjects. There were 39 qualifying subjects (72% male, 85% white, mean age of 27 years) with 36 completing all four Double-blind Treatment Periods.Methods. The four phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Data from in vitro studies have demonstrated that the formulation is difficult to prepare for injection [9]. Data from the combination of in vitro and in vivo studies have shown that it is difficult to reduce the particle size of Xtampza ER microspheres [8], the ER characteristics are maintained after manipulation [10], and that Xtampza ER has lower drug liking after chewing [29] and after intranasal administration [30] when compared with IR oxycodone.…”
Section: Discussionmentioning
confidence: 99%
“…Data from in vitro studies have demonstrated that the formulation is difficult to prepare for injection [9]. Data from the combination of in vitro and in vivo studies have shown that it is difficult to reduce the particle size of Xtampza ER microspheres [8], the ER characteristics are maintained after manipulation [10], and that Xtampza ER has lower drug liking after chewing [29] and after intranasal administration [30] when compared with IR oxycodone.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic profile of intranasally administered crushed oxycodone DETERx was assessed in nondependent subjects. Intranasal administration of crushed oxycodone DETERx did not result in higher peak plasma concentrations than did orally administered oxycodone DETERx, unlike that of intranasal administration of crushed IR oxycodone, which produced as much as twice the oxycodone C max (Table 2) [26]. The time to peak concentration was the same for both intranasal and oral administration of oxycodone DETERx [26], indicating that intranasal administration of oxycodone DETERx does not provide rapid increases in plasma concentrations (i.e., central exposure to oxycodone).…”
Section: Abuse Deterrencementioning
confidence: 99%
“…The intranasal abuse potential of oxycodone DETERx was assessed in a (category 3) randomized, double-blind, positive- and placebo-controlled crossover study [26]. The four treatments included oxycodone DETERx administered as either an intact oral capsule or a crushed intranasal preparation, IR oxycodone administered intranasally, and placebo.…”
Section: Abuse Deterrencementioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Support for this relationship has been demonstrated in studies of opioids, sedatives, and methylphenidate. [4][5][6][7][8] However, at the individual subject level, PK/PD correlations are often much weaker, suggesting that PK/PD relationships are highly variable and may depend on factors such as formulation or route of administration. 9,10 An extended-release (ER) tablet formulation of hydrocodone (Vantrela R ER; Teva Pharmaceuticals, Inc., Frazer, Pennsylvania) was developed using the CIMA R Abuse-Deterrence Technology platform to provide resistance against the rapid release of hydrocodone when tablets are manipulated or taken with alcohol.…”
mentioning
confidence: 99%